Optimalisasi Manajemen Akuntansi untuk Meningkatkan Kinerja Keuangan Perusahaan di Era Digital - Eksandy, Arry (CV. Lafadz Jaya, 2024)
Accounting management plays a crucial role in strategic decision-making that affects a company's financial performance. In the rapidly evolving digital era, optimizing accounting management through the use of information technology is key to enhancing efficiency and transparency in financial management. This paper aims to explore the main concepts of accounting management that can be optimized in the digital age to improve a company's financial performance. The focus of this study is on the implementation of cost control systems, efficient budgeting, and the utilization of information technology to accelerate the production of accurate and real-time financial reports. The analysis shows that integrating information technology into accounting management systems facilitates better financial data management, faster decision-making, and improved financial reporting transparency, ultimately having a positive impact on profitability and operational efficiency. The study suggests that companies, particularly in the manufacturing sector, should leverage technology to enhance accounting practices and maximize their financial performance.